Prevalence of needle stick injury and its associated factors among nursing staff working at a tertiary care hospital of North India - Aziz, Shazia; Akhter, Aisha; Akhter, Khurshida; Kachroo, Munira; Khan, Zahid Ali (International Journal of Research in Medical Sciences, 2023)
Background: Needle stick injury is a serious concern for healthcare workers as it poses a major risk for HIV, Hepatitis and other diseases transmission. The study aimed to determine the prevalence of NSI and its associated factors among nursing staff working at SKIMS, a tertiary care hospital of Kashmir, India. Methods: A descriptive cross-sectional study was conducted among 200 nurses working in different departments of SKIMS. Data regarding socio-demographic, various organizational and behavioral factors that may contribute to NSI, was collected using self-structured questionnaire and analysed using IBM statistical package for social sciences (SPSS), version 23. Results: The overall prevalence of NSI among nurses of SKIMS was 61% and it was 43.5% in the last 1 year. The nurses working for >40 hrs per week were found more at risk of NSI and it was more prevalent in young nurses with ≤5 years of experience. The nurses working in emergency unit were found more prone to NSI than the other units and recapping was found as the most common practice responsible for NSI. Post exposure to NSI, only 21.5% were found to wash the injury site with soap, water and applied antiseptics and most of them (75%) had not reported NSI to the concerned body. Conclusions: The magnitude of needlestick injury among nurses was high. Awareness generation regarding occupational health hazards of NSI, protective measures, the importance of reporting of incident and sharp management is the need of hour.